REVIEW ARTICLE: BENEFICIAL BACTERIA AND THEIR EFFECT ON THE IMMUNE SYSTEM - Jaafar, Salim Shamkhi; Jabber , Ehab Y. (PT. Antis International Publisher, 2025)
Objective: This study aimed to show some of the commensal species in the parts of the digestive system and their role in developing the immune system and other functions and their positive effect on the health of the host. Method: Molecular investigations have shown the presence of single, if not dozens of trillions of species, nutrients, and host cells. Results: The commensal bacteria in the digestive system play an important role in modifying and developing the immune system, as they provide environmental requirements of nutrients that protect the mucosal lining of the intestine, which in turn is affected by mutual interactions with the microbes of the digestive system. Novelty: Thus, the digestive system is considered one of the most complex systems due to the continuous interaction between the enormous number of microorganisms.